752. Geographic Analysis of Latent Tuberculosis Screening: A Health System Approach. (26th November 2018) - Bonnewell, John; Farrow, Laura; Dicks, Kristen; Cox, Gary; Stout, Jason E
Abstract: Background: Targeted testing and treatment of latent tuberculosis infection is a key element of tuberculosis (TB) elimination in the United States. In particular, foreign-born persons from TB-endemic countries are high priority for latent TB screening. Methods: We used the DEDUCE interface to query the electronic medical records of all patients presenting to Duke University Health System from January 1, 2010 to November 1, 2017. Latent tuberculosis screening was identified using CPT codes for the tuberculin skin test (TST) and/or interferon gamma release assays (IGRA). Patients' home addresses were mapped to census tracts; demographic data for these tracts were obtained from the American Community Survey. Higher-risk foreign born persons were defined as persons born in Africa, Asia, or Latin America. Results: Thirty-six thousand eight hundred and twenty-five patients received 48, 419 TSTs and 5, 366 received 5, 746 IGRAs during the study period. Excluding census tracts with fewer than 20 Health System patients (to reduce referral bias), census tracts with a higher proportion of higher risk residents had a greater proportion of Health System patients screened for latent TB ( P < 0.001, figure). Health system patients residing in census tracts with greater proportions of higher risk foreign born residents were more likely to be screened with TST than with an IGRA ( P < 0.001). Conclusion: Latent TB screening was significantly but weakly associated with a greater proportion of higher risk foreign born persons in a given census tract, and persons residing in such tracts were more likely to be screened with TST, which is not preferred due to cross-reaction with the BCG vaccine. Focusing latent TB screening on higher risk areas and using more IGRAs will be necessary to optimize TB prevention efforts. Disclosures: All authors: No reported disclosures.